Stomach content analysis of Monopterus albus Zuiew from swamp area of the Sawah Village, Kampar District, Riau Province - Resti Restari; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Monopterus albus is one of freshwater fishes that inhabitthe swamp area of Sawah Village, Riau. A research aim to understand the information of stomach content and its relation to size, sex and environmental condition has been done in March to May 2018.The fish was captured using fishing rods.Sampling was conducted 9 times in two months. The analysis was conducted using a volumetric method. Type of food present in the stomach content of the eel was analyzedas a basis to calculate the IP (Index Propenderence).There were 105 eels captured.Result shown the feed of M. albus consist of fish, mollusk, insects, and plants. The main food of M. albus was insect (IP 63%). There are same of main food in female, transition and male eels. The main food of female, transition, and male eels was insects. The water quality parameter are as follow : temperature 28-30oC, depth 60-75 cm, dissolved oxygen 4.3-4.5 mg/L, and pH 5-6. Based on data obtained it can be concluded that the Monopterus albus a carnivore fish. Keywords: Belut air tawar, makanan ikan, Index of Preponderance, ikan karnivora